Efficient Parking: A Smart System for Optimized Urban Mobility Using IoT - Lohith, E.; Priyanka, M. (INTI International University, 2024)
Internet of Things (IoT)-powered smart parking transforms urban transportation by combining cutting-edge technology to improve parking management. This system uses a network of Internet of Things (IoT) sensors that are mounted in parking spots to track availability in real-time. A centralized server receives the data gathered from these sensors, processes it, and updates the parking status instantly. The software has functions like digital payments, recommendation engines tailored to the user's tastes, and navigation to the closest spot. This minimizes emissions and traffic congestion, in addition to cutting down on the amount of time spent looking for parking. Furthermore, smart parking systems can maximize the use of available parking spaces and offer insightful data analytics to help city planners enhance urban infrastructure. All things considered, IoT-enabled smart parking systems are a big step in the direction of building smarter, more sustainable cities.